Feições de interação vulcano-sedimentares : seu uso como indicadores de contemporaneidade no magmatismo Rodeio Velho (meso-ordoviciano) e no vulcanismo Serra Geral (cretáceo inferior) - Petry, Karla (Universidade do Vale do Rio dos Sinos, 2006)
Volcanic-sedimentary interaction features were studied in association with two volcanic events: Rodeio Velho Magmatism (470 Ma), associated to Santa Bárbara and Guaritas allogroups (Camaquã Basin), at the localities of Arroio Carajá and Passo do Moinho; and Serra Geral Volcanism (average age of 130 Ma), associated to the Botucatu Formation (Paraná Basin), at Torres, São Sebastião do Caí and Feliz. The main methodology was field work, integrated with optical and electronic microscopy. Arroio Carajá shows a succession of two flows intercalated by sandstone and mudstone, and a sill at the contact surface of a flow and the sediment. Torres shows three cycles of sedimentation with volcanism and peperite formation. São Sebastião do Caí and Feliz show the contact between sedimentary rocks and a lava flow, with feeding intrusions at Feliz. Flow impressions indicate a pahoehoe flow over unconsolidated sediment. Injection peperite and clastic dyke are formed by the injection of sediment inwards the flow. Flow front peperite is formed by autobrecciation and bulldozing. Filling clastic dykes attest sediment migration. Xenoliths and apophasis indicate intrusion. The following features indicate undoubtfully the contemporaneity of sedimentation and flow: flow striation, ropy lava flow impression, crescent marks, flow front peperites and injection peperites and clastic dykes. It is possible to recon influence of the lava flows in the diagenesis of the sedimentary rocks. The interaction was with dry sediment, and recrystallization features are rare.
Keywords: Bacias sedimentares; Rochas sedimentares; Vulcanismo; Magmatismo; ACCNPQ::Ciências Exatas e da Terra::Geologia